The impact of past and present preferences on stimulus engagement in nursing home residents with dementia - Cohen-Mansfield, Jiska (2010)
OBJECTIVES: We examined engagement with stimuli in 193 nursing home residents with dementia. We hypothesized that activities and stimuli based on a person's past and current preferences would result in more engagement than other activities/stimuli. METHOD: The expanded version of the self-identity questionnaire [Cohen-Mansfield, J., Golander, H. & Arheim, G. (2000)] was used to determine participants' past/present interests (as reported by relatives) in the following areas: art, music, babies, pets, reading, television, and office work. We utilized the observational measurement of engagement (Cohen-Mansfield, J., Dakheel-Ali, M., & Marx, M.S. (2009). RESULTS: Analysis revealed that residents with current interests in music, art, and pets were more engaged by stimuli that reflect these interests than residents without these interests. CONCLUSION: Our findings demonstrate the utility of determining a person's preferences for stimuli in order to predict responsiveness. Lack of prediction for some stimuli may reflect differences between past preferences and activities that are feasible in the present.